A high-flux nanofiltration membrane with narrow pore size distribution, a preparation method thereof and a new pollutant treatment method
Patent Information
- Application Number
- CN202511473205.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-15
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-10-15
AI Technical Summary
[0007]上述专利对纳滤膜分离层微结构的调控虽然提升了膜分离效率,但存在制备方法复杂、结构不稳定和难以规模化应用等问题
(1)本发明通过对单体反应体系进行设计,在纳滤膜分离层中引入了刚性扭曲结构,提高了分离层自由体积,并利用空间位阻较小的多胺单体,窄化了膜孔径分布,同步提升了纳滤膜的渗透性和截留率。
Smart Images

Figure CN121130675B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of membrane separation technology, specifically relating to a high-flux nanofiltration membrane with narrow pore size distribution, its preparation method, and a new pollutant treatment method. Background Technology
[0002] New pollutants refer to toxic and hazardous chemicals released into the environment that possess characteristics such as biotoxicity, environmental persistence, and bioaccumulation, posing significant risks to the ecological environment or human health, but which are currently not included in management or whose existing management measures are insufficient. Currently, the new pollutants of great concern in the aquatic environment mainly include endocrine disruptors, pharmaceutically active compounds, perfluorinated compounds, brominated flame retardants, and polycyclic aromatic hydrocarbons. Nanofiltration, as a highly efficient membrane separation technology, has significant advantages such as high treatment precision and low energy consumption, demonstrating a strong competitive advantage in the removal of new pollutants from water bodies, and is an ideal next-generation water purification technology.
[0003] Existing commercial nanofiltration membranes are generally polyamide composite membranes prepared by interfacial polymerization, typically consisting of three parts: a nonwoven fabric layer, a porous support layer, and a polyamide separation layer. During membrane separation, the performance of interfacially polymerized nanofiltration membranes mainly depends on the microstructure of their separation layer. However, due to the rapid and uncontrollable nature of interfacial polymerization reactions, precise control over the separation layer structure is difficult. Existing commercial nanofiltration membranes have a relatively wide pore size distribution in their separation layer, leading to the preferential adsorption and enrichment of new pollutants such as small-molecule organic matter on the membrane's macroporous structure. This reduces porosity, ultimately resulting in a simultaneous decrease in membrane rejection and permeability.
[0004] By designing and developing nanofiltration membranes with narrow pore size distribution, not only can the retention capacity of composite membranes be improved, but also the effective separation area of the membrane can be increased or the water permeation resistance can be reduced, thereby simultaneously improving the retention performance and water flux of nanofiltration membranes.
[0005] Chinese patent document CN105854641A discloses a method for preparing a narrow-pore-distribution polyacrylonitrile nanofiltration membrane. The invention employs a phase inversion process, using a metal chloride salt aqueous solution as a solvent to prepare a polyacrylonitrile casting solution through solution polymerization. During the phase inversion process, metal ions and chloride ions gradually diffuse into the water, forming ion-induced pore water channels in the polyacrylonitrile membrane, thereby preparing a nanofiltration membrane with a narrow pore-distribution and good hydrophilicity.
[0006] Chinese patent document CN109999664A discloses a method for preparing a high-flux nanofiltration membrane with a narrow pore size distribution. The method employs an interfacial polymerization process, using piperazine, sodium camphor sulfonate, and dioxazoline chain extender to prepare an aqueous phase solution, and using aromatic polyacrylamide chloride to prepare an oil phase solution. Based on the interfacial polymerization reaction between the aqueous and oil phase solutions, a nanofiltration membrane with a narrow pore size distribution is prepared. The nanofiltration membrane prepared by this invention has a narrow pore size distribution, higher flux, and a high rejection rate for small molecule (molecular weight ≤200 Da) organic matter.
[0007] While the aforementioned patents have improved membrane separation efficiency by regulating the microstructure of the nanofiltration membrane separation layer, they also present problems such as complex preparation methods, unstable structures, and difficulty in large-scale application. Summary of the Invention
[0008] To address the shortcomings of existing technologies, this invention provides a method for preparing a high-flux nanofiltration membrane with a narrow pore size distribution. The prepared high-flux nanofiltration membrane with a narrow pore size distribution has both excellent water permeability and retention performance, as well as good antifouling performance, and has broad application prospects in wastewater treatment, especially in the treatment of new pollutants.
[0009] The specific technical solution adopted is as follows: A method for preparing a high-flux nanofiltration membrane with a narrow pore size distribution includes the following steps: (1) Using polyphenol monomers and polyamine monomers with rigid twisted structures as aqueous monomers, and adding an acid-binding agent to prepare a mixed monomer aqueous solution; the mass ratio of polyphenol monomers with rigid twisted structures to polyamine monomers is 20-1:1; (2) Prepare oil-phase solutions using acyl chloride oil-phase monomers or chlorocyanide oil-phase monomers; (3) Interfacial polymerization reaction is carried out on the polymer ultrafiltration membrane using a mixed monomer aqueous solution and an oil solution, and crosslinking is performed after the reaction to obtain the high-flux nanofiltration membrane with narrow pore size distribution. The polyphenol monomer with a rigid twisted structure is selected from at least one of bisphenol fluorene, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 3,3,3',3'-tetramethyl-1,1'-spirobinobi(indane)-6,6'-diol and 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobinobiindane; The polyamine monomer is selected from at least one of piperazine, o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, ethylenediamine, diethylenetriamine, and triethylenetetramine.
[0010] This invention is based on the "reaction-diffusion" mechanism of interfacial polymerization. By adjusting the structure and composition of the reactant monomers, the microstructure of the resulting nanofiltration membrane separation layer is controlled. Specifically, by mixing polyphenol monomers containing rigid twisted structures and small molecule polyamine monomers to form a multi-component aqueous monomer, this process introduces a rigid twisted structure into the membrane separation layer, making it difficult for the polymer crosslinking network to stack, thereby increasing the free volume of the separation layer. At the same time, the small molecule polyamine monomers have less steric hindrance, which can further reduce the pore size at the macropores in the membrane separation layer, achieving a narrower pore size distribution, thereby simultaneously improving the permeability and rejection rate of the nanofiltration membrane.
[0011] Further preferably, the polyphenol monomer with a rigid twisted structure is 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobine, and the polyamine monomer is piperazine.
[0012] Preferably, the acid-binding agent is at least one of potassium hydroxide, sodium hydroxide, pyridine, triethylamine, N,N-diisopropylethylamine, sodium carbonate, and trisodium phosphate dodecahydrate; the mass concentration of the acid-binding agent in the mixed monomer aqueous solution is 0.1-5 wt%.
[0013] Preferably, the acyl chloride oil phase monomer is at least one of pyromellitic terephthaloyl chloride and isophthaloyl chloride, and the chlorocyanide oil phase monomer is cyanuric chloride; the solvent in the oil phase solution is at least one of Isopar G, n-hexane and toluene.
[0014] Furthermore, the total mass concentration of aqueous monomers in the mixed monomer aqueous solution is 1-10 wt%; the mass concentration of oil monomers in the oil solution is 0.1-5 wt%.
[0015] Preferably, the polymer ultrafiltration membrane is any one of polysulfone ultrafiltration membrane, polyethersulfone ultrafiltration membrane, polyacrylonitrile ultrafiltration membrane, cellulose acetate ultrafiltration membrane, polyethylene ultrafiltration membrane, and polyamide ultrafiltration membrane.
[0016] Furthermore, in step (3), after the polymer ultrafiltration membrane is wetted with the mixed monomer aqueous solution, the excess solution on the membrane surface is removed, and then the oil phase solution is placed on the surface of the polymer ultrafiltration membrane to allow the oil phase monomer and the aqueous phase monomer to undergo an interfacial polymerization reaction.
[0017] Furthermore, the polymer ultrafiltration membrane was impregnated at room temperature for 1-10 min using a mixed monomer aqueous solution; the interfacial polymerization reaction conditions were: room temperature, 1-10 min.
[0018] Furthermore, after the interfacial polymerization reaction is completed, the membrane surface is rinsed 1-5 times with an oil-phase solvent, and the resulting nascent membrane is placed in an oven for crosslinking.
[0019] Preferably, the crosslinking temperature is 50-100℃ and the crosslinking time is 1-15 min.
[0020] The present invention also provides a method for preparing a high-flux nanofiltration membrane with a narrow pore size distribution, which yields the high-flux nanofiltration membrane with a narrow pore size distribution.
[0021] This high-flux nanofiltration membrane with a narrow pore size distribution exhibits a narrow pore size distribution and high flux, as well as a high rejection rate for novel small-molecule pollutants. Its average pore size is ≤1 nm, and the geometric standard deviation of the pore size distribution σ is [not specified in the original text]. p <1.3 (σ p The smaller the aperture, the narrower the pore size distribution; pure water flux ≥ 15 L·m -2 ·h -1 ·bar -1 The rejection rate for new small molecule pollutants is ≥90%.
[0022] The present invention also provides the application of the high-flux nanofiltration membrane with the narrow pore size distribution in the field of water treatment.
[0023] The present invention also provides a new pollutant treatment method, wherein the new pollutant is tetracycline, and the method utilizes the high-flux nanofiltration membrane with narrow pore size distribution.
[0024] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) By designing the monomer reaction system, the present invention introduces a rigid tortuous structure into the nanofiltration membrane separation layer, which increases the free volume of the separation layer, and utilizes polyamine monomers with small steric hindrance to narrow the membrane pore size distribution, thereby simultaneously improving the permeability and rejection rate of the nanofiltration membrane.
[0025] (2) The nanofiltration membrane preparation method of the present invention is simple, has a short process flow, strong controllability, low equipment requirements, and is easy to mass-produce.
[0026] (3) The high-flux nanofiltration membrane with narrow pore size distribution provided by the present invention has a high flux, which can effectively improve water treatment efficiency, save treatment time and reduce treatment cost.
[0027] (4) The high-flux nanofiltration membrane with narrow pore size distribution provided by the present invention can be widely used in drinking water purification and sewage treatment, etc. It has a good interception effect on new pollutants such as antibiotics, and the stability test results show that it has good anti-pollution performance and has broad prospects for industrial application. Attached Figure Description
[0028] Figure 1 The image shows a surface electron microscope (TEM) image of the high-throughput nanofiltration membrane with narrow pore size distribution prepared in Example 2.
[0029] Figure 2The image shows a surface electron microscope (TEM) image of the high-throughput nanofiltration membrane with narrow pore size distribution prepared in Example 4. Detailed Implementation
[0030] To make the objectives, features, and advantages of this invention more apparent and understandable, a detailed description is provided below through specific embodiments. Many specific details are set forth in the following description to provide a thorough understanding of the invention. However, the invention can be practiced in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below. Technical features in various embodiments of the invention can be combined appropriately without mutual conflict.
[0031] Unless otherwise specified, the operating methods in the following examples are generally performed under conventional conditions or as recommended by the manufacturer. Contents not described in detail in this specification are prior art known to those skilled in the art. Unless otherwise specified, the experimental materials used in the examples below can be purchased from conventional biochemical reagent companies.
[0032] Example 1 A mixed monomer aqueous solution containing 3.0 wt% bisphenol fluorene, 0.3 wt% piperazine, and 1.5 wt% sodium hydroxide was poured onto the surface of a fixed polyacrylonitrile ultrafiltration membrane. After wetting at room temperature for 5 minutes, the mixed monomer aqueous solution was discarded, and the residual solution on the surface of the polyacrylonitrile ultrafiltration membrane was removed using a rubber roller. Then, a mixed monomer aqueous solution containing 0.3 wt% trimesoyl chloride in n-hexane was poured onto the surface of the polyacrylonitrile ultrafiltration membrane for interfacial polymerization. The reaction was carried out at room temperature for 2 minutes. Afterward, the oil phase solution was discarded, and the membrane surface was rinsed three times with the oil phase solvent n-hexane to obtain a nascent membrane. Finally, the nascent membrane was placed in an oven at 85°C for post-treatment and kept at that temperature for 10 minutes before being removed, thus obtaining the high-flux nanofiltration membrane with a narrow pore size distribution.
[0033] Tests show that the pure water flux of this high-flux nanofiltration membrane with narrow pore size distribution is 20.1 L·m. -2 ·h -1 ·bar -1 (Test temperature was 25℃, test pressure was 0.5 MPa), the rejection rate for the new pollutant tetracycline (concentration of 10 ppm) was 95.2%, and the rejection rate for tetracycline (concentration of 10 ppm) was 94.5% in the 24-hour long-term stability test.
[0034] Example 2 A mixed monomer aqueous solution containing 2.0 wt% 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobisindane, 0.2 wt% piperazine, and 2.0 wt% sodium hydroxide was poured onto the surface of a fixed polyacrylonitrile ultrafiltration membrane. After wetting at room temperature for 5 min, the mixed monomer aqueous solution was discarded, and the residual solution on the surface of the polyacrylonitrile ultrafiltration membrane was removed using a rubber roller. Then, a mixed monomer aqueous solution containing 0.2 wt% trimesoyl chloride in n-hexane was poured onto the surface of the polyacrylonitrile ultrafiltration membrane for interfacial polymerization. The reaction was carried out at room temperature for 3 min. Afterward, the oil phase solution was discarded, and the membrane surface was rinsed twice with the oil phase solvent n-hexane to obtain a nascent membrane. Finally, the nascent membrane was placed in an oven at 85℃ for post-treatment and kept at that temperature for 10 min before being removed, thus obtaining the high-flux nanofiltration membrane with a narrow pore size distribution. Its surface electron micrograph is shown below. Figure 1 As shown.
[0035] Tests show that the pure water flux of this high-flux nanofiltration membrane with narrow pore size distribution is 18.5 L·m. -2 ·h -1 ·bar -1 (Test temperature was 25℃, test pressure was 0.5 MPa), the rejection rate for the new pollutant tetracycline (concentration of 10 ppm) was 97.5%, and the rejection rate for tetracycline (concentration of 10 ppm) was 96.5% in the 24-hour long-term stability test.
[0036] Example 3 A mixed monomer aqueous solution containing 1.0 wt% bisphenol fluorene, 1.0 wt% m-phenylenediamine, and 0.5 wt% triethylamine was poured onto the surface of a fixed polysulfone ultrafiltration membrane. After wetting at room temperature for 3 minutes, the mixed monomer aqueous solution was discarded, and the residual solution on the surface of the polysulfone ultrafiltration membrane was removed using a rubber roller. Then, a mixed monomer aqueous solution containing 0.5 wt% isophthaloyl chloride and Isopar G was poured onto the surface of the polysulfone ultrafiltration membrane for interfacial polymerization. The reaction was carried out at room temperature for 4 minutes. Afterward, the oil phase solution was discarded, and the membrane surface was rinsed twice with the oil phase solvent Isopar G to obtain a nascent membrane. Finally, the nascent membrane was placed in an oven at 75°C for post-treatment and kept at that temperature for 10 minutes before being removed, thus obtaining the high-flux nanofiltration membrane with a narrow pore size distribution.
[0037] Tests show that the pure water flux of this high-flux nanofiltration membrane with narrow pore size distribution is 15.8 L·m. -2 ·h -1 ·bar -1(Test temperature was 25℃, test pressure was 0.5 MPa), the rejection rate of the new pollutant tetracycline (concentration of 10 ppm) was 98.7%, and the rejection rate of tetracycline (concentration of 10 ppm) was 97.1% in the 24-hour long-term stability test.
[0038] Example 4 A mixed monomer aqueous solution containing 2.0 wt% 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobisindane, 0.1 wt% piperazine, and 2.0 wt% potassium hydroxide was poured onto the surface of a fixed polyacrylonitrile ultrafiltration membrane. After wetting at room temperature for 5 min, the mixed monomer aqueous solution was discarded, and the residual solution on the surface of the polyacrylonitrile ultrafiltration membrane was removed using a rubber roller. Then, a mixed monomer aqueous solution containing 0.2 wt% cyanuric chloride in toluene was poured onto the surface of the polyacrylonitrile ultrafiltration membrane for interfacial polymerization. The reaction was carried out at room temperature for 4 min. Afterward, the oil phase solution was discarded, and the membrane surface was rinsed three times with toluene, the oil phase solvent, to obtain a nascent membrane. Finally, the nascent membrane was placed in an oven at 80℃ for post-treatment. After holding at this temperature for 5 min, it was removed, yielding the high-flux nanofiltration membrane with a narrow pore size distribution. Its surface electron micrograph is shown below. Figure 2 As shown.
[0039] Tests showed that the pure water flux of this high-flux nanofiltration membrane with narrow pore size distribution was 23.1 L·m⁻¹. -2 ·h -1 ·bar -1 (Test temperature was 25℃, test pressure was 0.5 MPa), the rejection rate for the new pollutant tetracycline (concentration of 10 ppm) was 96.1%, and the rejection rate for tetracycline (concentration of 10 ppm) was 95.5% in the 24-hour long-term stability test.
[0040] Example 5 A mixed monomer aqueous solution containing 4.0 wt% bisphenol fluorene, 0.2 wt% ethylenediamine, and 1.0 wt% sodium carbonate was poured onto the surface of a fixed polyethersulfone ultrafiltration membrane. After wetting at room temperature for 5 minutes, the mixed monomer aqueous solution was discarded, and the residual solution on the surface of the polyethersulfone ultrafiltration membrane was removed using a rubber roller. Then, a mixed monomer aqueous solution containing 1.0 wt% terephthaloyl chloride in n-hexane was poured onto the surface of the polyethersulfone ultrafiltration membrane for interfacial polymerization. The reaction was carried out at room temperature for 3 minutes. Afterward, the oil phase solution was discarded, and the membrane surface was rinsed three times with the oil phase solvent n-hexane to obtain a nascent membrane. Finally, the nascent membrane was placed in an oven at 80°C for post-treatment and kept at that temperature for 10 minutes before being removed, thus obtaining the high-flux nanofiltration membrane with a narrow pore size distribution.
[0041] Tests showed that the pure water flux of this high-flux nanofiltration membrane with narrow pore size distribution was 32.1 L·m. -2 ·h -1 ·bar -1 (Test temperature was 25℃, test pressure was 0.5 MPa), the rejection rate for the new pollutant tetracycline (concentration of 10 ppm) was 90.8%, and the rejection rate for tetracycline (concentration of 10 ppm) was 90.0% in the 24-hour long-term stability test.
[0042] Example 6 A mixed monomer aqueous solution containing 1.5 wt% 3,3,3',3'-tetramethyl-1,1'-spirobyl (indane)-6,6'-diol, 0.5 wt% diethylenetriamine, and 3.0 wt% sodium hydroxide was poured onto the surface of a fixed polyacrylonitrile ultrafiltration membrane. After wetting at room temperature for 5 min, the mixed monomer aqueous solution was discarded, and the residual solution on the surface of the polyacrylonitrile ultrafiltration membrane was removed using a rubber roller. Then, a mixed monomer aqueous solution containing 0.2 wt% trimesoyl chloride in n-hexane was poured onto the surface of the polyacrylonitrile ultrafiltration membrane for interfacial polymerization. The reaction was carried out at room temperature for 5 min. Afterward, the oil phase solution was discarded, and the membrane surface was rinsed three times with the oil phase solvent n-hexane to obtain a nascent membrane. Finally, the nascent membrane was placed in an oven at 85°C for post-treatment, and after holding at this temperature for 5 min, it was removed to obtain the high-flux nanofiltration membrane with a narrow pore size distribution.
[0043] Tests showed that the pure water flux of this high-flux nanofiltration membrane with narrow pore size distribution was 28.3 L·m. -2 ·h -1 ·bar -1 (Test temperature was 25℃, test pressure was 0.5 MPa), the rejection rate for the new pollutant tetracycline (concentration of 10 ppm) was 91.2%, and the rejection rate for tetracycline (concentration of 10 ppm) was 90.1% in the 24-hour long-term stability test.
[0044] Comparative Example 1 An aqueous solution containing 3.0 wt% bisphenol fluorene and 1.5 wt% sodium hydroxide was poured onto the surface of a fixed polyacrylonitrile ultrafiltration membrane. After soaking for 5 min at room temperature, the aqueous solution was discarded, and the residual solution on the surface of the polyacrylonitrile ultrafiltration membrane was removed using a rubber roller. Then, an oil-phase solution containing 0.3 wt% trimesoyl chloride in n-hexane was poured onto the surface of the polyacrylonitrile ultrafiltration membrane for interfacial polymerization. The reaction was carried out at room temperature for 2 min. Afterward, the oil-phase solution was discarded, and the membrane surface was rinsed three times with the oil-phase solvent n-hexane to obtain a nascent membrane. Finally, the nascent membrane was placed in an oven at 85℃ for post-treatment and kept at that temperature for 10 min before being removed to obtain the nanofiltration membrane.
[0045] Tests show that the pure water flux of this nanofiltration membrane is 19.5 L·m. -2 ·h -1 ·bar -1 (Test temperature was 25℃, test pressure was 0.5 MPa). The rejection rate for the new pollutant tetracycline (concentration of 10 ppm) was 75.6%, and the rejection rate for tetracycline (concentration of 10 ppm) was 40.2% in the 24-hour long-term stability test.
[0046] Compared with Example 1, this comparative example only added a polyphenol monomer with a rigid tortuous structure to the aqueous solution. The resulting separation layer was looser and had a wider pore size distribution. New pollutants could easily permeate through the membrane and be adsorbed at the macropore structure of the membrane, further aggravating membrane fouling and resulting in poor retention performance of the obtained nanofiltration membrane.
[0047] Comparative Example 2 An aqueous solution containing 1.0 wt% m-phenylenediamine and 0.5 wt% triethylamine was poured onto the surface of a fixed polysulfone ultrafiltration membrane. After wetting at room temperature for 3 min, the aqueous solution was discarded, and the residual solution on the surface of the polysulfone ultrafiltration membrane was removed using a rubber roller. Then, an oil-phase solution containing 0.5 wt% isophthaloyl chloride and Isopar G was poured onto the surface of the polysulfone ultrafiltration membrane for interfacial polymerization. The reaction was carried out at room temperature for 4 min. Afterward, the oil-phase solution was discarded, and the membrane surface was rinsed twice with the oil-phase solvent Isopar G to obtain a nascent membrane. Finally, the nascent membrane was placed in a 75°C oven for post-treatment, and after holding at this temperature for 10 min, it was removed to obtain the nanofiltration membrane.
[0048] Tests show that the pure water flux of this nanofiltration membrane is 2.8 L·m. -2 ·h -1 ·bar -1 (Test temperature was 25℃, test pressure was 0.5 MPa), the rejection rate for the new pollutant tetracycline (concentration of 10 ppm) was 97.6%, and the rejection rate for tetracycline (concentration of 10 ppm) was 80.2% in the 24-hour long-term stability test.
[0049] Compared with Example 3, this comparative example only added small molecule polyamine monomers to the aqueous solution, resulting in a smaller free volume and greater thickness of the separation layer. This led to poor permeability of the obtained nanofiltration membrane, exacerbated the concentration polarization phenomenon of new pollutants on the membrane surface, and reduced the membrane's antifouling performance.
[0050] The embodiments described above provide a detailed explanation of the technical solutions of the present invention. It should be understood that the above descriptions are merely specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, additions, or similar substitutions made within the scope of the principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a high-flux nanofiltration membrane with a narrow pore size distribution, characterized in that, Includes the following steps: (1) Using polyphenol monomers and polyamine monomers with rigid twisted structures as aqueous monomers, and adding an acid-binding agent to prepare a mixed monomer aqueous solution; the mass ratio of polyphenol monomers with rigid twisted structures to polyamine monomers is 20-1:1; (2) Prepare oil-phase solutions using acyl chloride oil-phase monomers or chlorocyanide oil-phase monomers; (3) Interfacial polymerization reaction is carried out on the polymer ultrafiltration membrane using a mixed monomer aqueous solution and an oil solution, and crosslinking is performed after the reaction to obtain the high-flux nanofiltration membrane with narrow pore size distribution. The polyphenol monomer with a rigid twisted structure is selected from at least one of bisphenol fluorene, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 3,3,3',3'-tetramethyl-1,1'-spirobinobi(indane)-6,6'-diol and 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobinobiindane; The polyamine monomer is selected from at least one of piperazine, o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, ethylenediamine, diethylenetriamine, and triethylenetetramine.
2. The method for preparing a high-flux nanofiltration membrane with narrow pore size distribution according to claim 1, characterized in that, The acid-binding agent is at least one of potassium hydroxide, sodium hydroxide, pyridine, triethylamine, N,N-diisopropylethylamine, sodium carbonate, and trisodium phosphate dodecahydrate; in the aqueous phase solution of the mixed monomers, the mass concentration of the acid-binding agent is 0.1-5 wt%.
3. The method for preparing a high-flux nanofiltration membrane with narrow pore size distribution according to claim 1, characterized in that, The acyl chloride oil phase monomer is at least one of pyromellitic trimethylbenzene chloride, terephthaloyl chloride, and isophthaloyl chloride, and the chlorocyanide oil phase monomer is cyanuric chloride; the solvent in the oil phase solution is at least one of Isopar G, n-hexane, and toluene.
4. The method for preparing a high-flux nanofiltration membrane with narrow pore size distribution according to claim 1, characterized in that, The total mass concentration of aqueous monomers in the mixed monomer aqueous solution is 1-10 wt%; the mass concentration of oil monomers in the oil solution is 0.1-5 wt%.
5. The method for preparing a high-flux nanofiltration membrane with narrow pore size distribution according to claim 1, characterized in that, The polymer ultrafiltration membrane is any one of polysulfone ultrafiltration membrane, polyethersulfone ultrafiltration membrane, polyacrylonitrile ultrafiltration membrane, cellulose acetate ultrafiltration membrane, polyethylene ultrafiltration membrane, and polyamide ultrafiltration membrane.
6. The method for preparing a high-flux nanofiltration membrane with narrow pore size distribution according to claim 1, characterized in that, After wetting the polymer ultrafiltration membrane with a mixed monomer aqueous solution, the excess solution on the membrane surface is removed, and then an oil phase solution is placed on the surface of the polymer ultrafiltration membrane to allow the oil phase monomer and the aqueous phase monomer to undergo an interfacial polymerization reaction.
7. The method for preparing a high-flux nanofiltration membrane with narrow pore size distribution according to claim 1, characterized in that, The cross-linking temperature is 50-100℃, and the cross-linking time is 1-15 min.
8. The high-flux nanofiltration membrane with narrow pore size distribution prepared by the method for preparing a high-flux nanofiltration membrane with narrow pore size distribution according to any one of claims 1-7, characterized in that, Its average pore size is ≤1 nm, and the geometric standard deviation of pore size distribution is σ. p <1.
3.
9. The application of the high-flux nanofiltration membrane with narrow pore size distribution according to claim 8 in the field of water treatment.
10. A novel pollutant treatment method, characterized in that, The new pollutant is tetracycline, and the high-flux nanofiltration membrane with narrow pore size distribution as described in claim 8 is used.
Citation Information
Patent Citations
Method for preparing narrow-hole-diameter-distribution polyacrylonitrile nano-filtration membrane
CN105854641A
Preparation method of nanofiltration membrane with narrow pore size distribution and large throughout
CN109999664A
High-performance composite solvent-resistant nanofiltration membrane with rigid twisted non-planar structure polyamide layer and preparation method of high-performance composite solvent-resistant nanofiltration membrane
CN119793230A
Composite nanofiltration membrane based on rigid torsion phenol amine monomer as well as preparation method and application of composite nanofiltration membrane
CN120268254A